2010
DOI: 10.1016/j.actatropica.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a successful schistosomiasis control programme in Cambodia (1995–2006)

Abstract: Following preventive chemotherapy covering the entire population in the two endemic regions in Cambodia, the prevalence of schistosomiasis dropped from 77% in 1995 to 0.5% in 2003. The study presented here reports on the running cost of the control programme, and evaluates its cost-effectiveness and cost-benefit. Financial costs were assessed using data taken from the annual reports of the National Center for Malaria Control, the Cambodian institution responsible for the control activities. Other data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…We assumed that praziquantel has a S. haematobium curative rate of 55% (range 37%–90%), as is consistent with epidemiological data (19,21,2326). For women who received praziquantel as a child and those without established FGS, we assumed that they have a reduced risk of 50% (range 40%–70%) of developing FGS (20).…”
Section: Methodssupporting
confidence: 64%
“…We assumed that praziquantel has a S. haematobium curative rate of 55% (range 37%–90%), as is consistent with epidemiological data (19,21,2326). For women who received praziquantel as a child and those without established FGS, we assumed that they have a reduced risk of 50% (range 40%–70%) of developing FGS (20).…”
Section: Methodssupporting
confidence: 64%
“…We included 84 English studies and six French studies. One study (Colley 2013), which was retrieved through an updated search, provided recent data for studies retrieved previously (Coulibaly 2011; Shane 2011; Tchuente 2012). In this case, we gathered data for the 2 × 2 tables from the most recent publication (Colley 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of a suitable gold standard for active schistosomiasis is reflected in the existing literature, where different reference standards are used with subsequent variation in accuracy (especially with specificity) of the index test (Koukounari 2009; Coulibaly 2011; Tchuente 2012; Colley 2013; Erko 2013; King 2013;Lodh 2013; Sousa-Figueiredo 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, evidence demonstrating the ability of MDA to control the transmission of schistosomiasis in high prevalence areas is mixed, in part because the impact of MDA will vary across different epidemiological settings. There are many regions, such as the Mekong River in Cambodia, where excellent progress has been made, with heavy-intensity infections reduced to below 1% [5, 6]. However, several recent studies in Africa have demonstrated limited progress in reducing prevalence in localized high-transmission areas, despite high MDA coverage [79].…”
Section: Introductionmentioning
confidence: 99%